Automatic Compact High-Speed Industrial Postal Canceling Machine - Efren Diez-Jimenez; Diego Lopez-Pascual; Miguel Fernandez-Munoz; Jesus del-Olmo-Anguix; Ignacio Valiente-Blanco; Oscar Manzano-Narro; Angel Villacastin-Sanchez; Bernardo Alarcos (Machines)
In this work, we describe the mechanical design, analysis, and tests of an innovative automatic high-speed industrial postal canceling machine. The main novelties of this machine are automatic feeding of heterogeneous letters in a very compact design, high speed of letter processing (>22,000 letters per hour), and letter jamming detection. This is the first time that such an industrial and automatic machine is being constructed in a reduced desktop size and is able to handle heterogeneous types of letters at a high-speed rate. The cancel machine includes a linear feeding belt for the letter feeding, assisted by a vacuum letter gripper and a set of conveyor belts that guide the letter to the impression. The machine has low energy consumption and is easy to maintain with multiple safety limit switches. The design is fully compliant with the new European machine regulations. We show the details of the mechanical design, and we present several performance and speed tests, demonstrating that the machine achieves more than 99.8% of canceling rate with different sizes and thicknesses of letters, padded and mixed-size, while having a letter canceling speed of more than 22,000 letters per hour.